2020
DOI: 10.1016/j.drugalcdep.2019.107741
|View full text |Cite|
|
Sign up to set email alerts
|

A repeated cross-sectional study of factors associated with pregabalin-positive poisoning deaths in Ireland

Abstract: The National Drug-Related Deaths Index (NDRDI) reports on poisoning deaths (also known as overdose), which are deaths in the general population due to the toxic effect of a drug or combination of drugs, and on non-poisonings, which are deaths as a result of trauma, such as hanging, or medical reasons, such as cardiac events, among people who use drugs. The latest figures from the NDRDI show that 376 people died in 2017 from poisoning deaths and that 410 non-poisoning deaths occurred among people who used drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…Most of these studies were based on post-mortem data but some were generated by data from suspected DUID cases. An Irish study found an increase in pregabalin-positive poisoning deaths from 5% of all cases in 2013 to 26% in 2016 [51]. The odds of being pregabalin positive increased with female sex, opioid misuse, recent treatment for problem drug use, and the year of death.…”
Section: Forensic Toxicologymentioning
confidence: 99%
See 3 more Smart Citations
“…Most of these studies were based on post-mortem data but some were generated by data from suspected DUID cases. An Irish study found an increase in pregabalin-positive poisoning deaths from 5% of all cases in 2013 to 26% in 2016 [51]. The odds of being pregabalin positive increased with female sex, opioid misuse, recent treatment for problem drug use, and the year of death.…”
Section: Forensic Toxicologymentioning
confidence: 99%
“…Using this method for ranking the safety of 70 pharmaceuticals, pregabalin and gabapentin were ranked in the middle. An Irish study found an increase in the pregabalin poisoning deaths from 2013 to 2016 [51]. For gabapentin, it is still somewhat controversial whether a substantial overdose of gabapentin used alone is enough to induce life-threatening respiratory or cardiac insufficiency.…”
Section: Risks With Abuse Of Gabapentinoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…54 A study conducted in Ireland explored the association between opioid use and treatment for problem drug use and pregabalin-positive poisoning death. 55 Therefore, it is likely that the co-prescribing of opioids or substance misuse and abuse is also a major risk factor to the increased drug-related death in gabapentinoid users in the UK. Nevertheless, the association between gabapentinoid utilisation patterns (e.g.…”
Section: Discussionmentioning
confidence: 99%